Diversification of Local Food Products through Banana Heart Processing - Nurliani; Suherah; Agustrai; Mukhlis (Unram Journal of Community Service, 2025)
The demand for animal protein is increasing in line with public awareness of the importance of balanced nutrition, population growth, and increased purchasing power. Satay and shredded meat are popular foods that are sources of animal protein. The price of meat continues to rise, prompting people to seek alternative products that are less expensive to produce yet still nutritious. Processing banana hearts into banana heart satay can be an alternative solution. The "Mekar Bersama" Women Farmers Group is one of the community groups in Maros Regency that partners with us to provide education, training, and assistance in processing local agricultural products into creative, affordable, and nutritious food products. The program solution implemented is the Community Service Program (PkM), which includes education on the benefits and nutritional value of consuming banana hearts, as well as demonstrations of techniques for processing banana hearts into plant-based satay. The results of the activities showed an average increase of 66.67% in the knowledge and skills of the partners. The partners enhanced their understanding of the benefits and nutritional content of banana hearts, gained knowledge about the environment, and developed skills in processing banana hearts into vegetable satay.